Price cycles in Perth petrol markets: A spectral analysis - Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2008)
Numerous commentators have noted the tendency of retail petroleum prices to cycle. This paper undertakes a formal analysis of petroleum price cycles, using spectral analysis to uncover which cycles are most important, and regression analysis to ascertain what drives that importance.